(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Indo-Myanmar cross border trade has always been governed by the kind of human groups that live in the border area. The socio-economy of the border area is always of supplementary and complementary in nature and this aspect of economy should always be kept in mind while promoting the border trade. The research is intended to examine the impact on the socio economic affairs of Moreh due to cross border trade. Statistical analysis has been applied on the data collected by the researcher to examine the impact of cross border trade on socio economic parameters i.e., education, occupation and income. Along with this, other socio-economic parameters have also been examined theoretically to analyse the impact of cross border trade. The statistical analysis has shown a significant association among the three parameters and the positive impact that cross border trade has brought in since its formalisation. The theoretical analysis also supports the same results. The identified socio-economic and demographic variables from the present study that have been conducted in Moreh town of Tengnoupal district of Manipur will help in boosting the cross border trade between the two countries and the overall development of border towns.